Analysis of the Impact of Productive Zakat in Empowering Mustahiq's Economic Welfare in Jember Regency - Saedi Saedi; Moch Chotib; Siti Masrohatin (Jurnal Syntax Admiration, 2024)
The purpose of this study is to analyze the distribution of Productive Zakat in NU Care-LAZISNU PCNU Jember in empowering mustahiq economic welfare in Jember Regency. This research uses a qualitative approach, and this research is descriptive. Qualitative research methods are research that produces descriptive data in the form of written or spoken words of people or observable behavior. NU Care-LAZISNU Jember has several steps to be able to carry out the mandate of distributing productive zakat so that the target and goal of distributing productive zakat is achieved. As a result, NU Care LAZISNU JEMBER uses a distribution pattern with zakat management functions consisting of forcasting, planing, organizing and actuating and controling. While the utilization model used is in kind by providing business tools and capital assistance such as livestock. The impact felt by mustahiq who receive productive zakat can be seen from several indicators including increased income, more decent housing or housing, and increased education and health levels.